Electrochemical device and electronic device

By using a combination of a first positive electrode active material containing Ni and Mn and a second positive electrode active material containing Ni and Co in the electrochemical device, the safety problem of high nickel ternary material at high voltage and high temperature is solved, and the safety problem of high nickel ternary material is achieved. It combines high energy density and safety performance, and improves circulation performance and structural stability.

CN119213578AActive Publication Date: 2024-12-27NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202380039261.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2024-12-27
Estimated Expiration
2043-10-20

AI Technical Summary

Technical Problem

The poor thermal stability of high-nickel ternary materials leads to a reduced safety, limiting the widespread application of high-nickel ternary materials in electrochemical devices, especially under high voltage and high temperature conditions.

Method used

A positive electrode sheet is adopted, including a layer composed of the first and second positive electrode active materials. The first positive electrode active material contains Ni and Mn and the second positive electrode active material contains Ni and Co., and by regulating the relative content and structure of the material, electricity is ensured. The chemical device has high reversible discharge capacity and structural stability in the high voltage zone, reducing the risk of excessive deliquency, and suppressing oxygen release through surface oxygen vacancies, improving circulation and safety performance.

Benefits of technology

It realizes the balance of high energy density and safety performance of electrochemical devices, improves circulation and safety performance, and ensures structural stability and discharge capacity under high temperature and high voltage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213578A_ABST
    Figure CN119213578A_ABST
Patent Text Reader

Abstract

The invention provides an electrochemical device and an electronic device. The electrochemical device comprises a positive pole piece. The positive pole piece comprises a positive active material layer, and the positive active material layer comprises a first positive active material and a second positive active material. The first positive electrode active material contains Ni element and Mn element, and the second positive electrode active material contains Ni element and Co element. The relation curve of the discharge capacity voltage differential dQ / dV of the electrochemical device and the voltage V at least comprises two peaks above 3.8 V. The electrochemical device provided by the invention has good cycle performance and safety performance while meeting the requirement of high energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy storage, and in particular to electrochemical devices and electronic devices. Background Art

[0002] With the development of electrochemical energy storage technology, higher and higher requirements are placed on the energy density and safety performance of electrochemical devices (e.g., lithium-ion batteries). For example, with the increasing demand for long driving range in the power battery market, high-energy-density high-nickel ternary materials have gradually become one of the development hotspots. However, with the increase in nickel content, the thermal stability of ternary materials deteriorates, which reduces the safety of high-nickel ternary materials and limits the widespread application of high-nickel ternary materials. Summary of the invention

[0003] In view of this, the present application provides an electrochemical device and an electronic device to improve the safety of the electrochemical device while meeting the high energy density requirements of the electrochemical device.

[0004] In a first aspect of the present application, an electrochemical device is provided, the electrochemical device comprising a positive electrode plate. The positive electrode plate comprises a positive electrode active material layer, the positive electrode active material layer comprises a first positive electrode active material and a second positive electrode active material. The first positive electrode active material comprises Ni element and Mn element, and the second positive electrode active material comprises Ni element and Co element. The relationship curve between the capacity voltage differential dQ / dV and the voltage V of the electrochemical device discharge contains at least two peaks above 3.8V. In the electrochemical device of the present application, the first positive electrode active material has a characteristic peak in the high voltage region of the relationship curve of the capacity-voltage differential dQ / dV and the voltage V during the discharge of the electrochemical device, relative to the second positive electrode active material, which can enable the electrochemical device to have a higher reversible discharge capacity in the high voltage region, thereby meeting the high energy density requirement of the electrochemical device; at the same time, since the amount of lithium desorption of the first positive electrode active material in the high voltage region is relatively high, the risk of excessive lithium desorption of the second positive electrode active material can be reduced, thereby improving the structural stability of the second positive electrode active material at high temperature and high voltage, and due to the presence of oxygen vacancies on the surface of the first positive electrode active material itself, its surface oxygen release can be inhibited, so that it still has a higher structural stability at high temperature and high voltage, thereby greatly improving the cycle performance and safety performance of the electrochemical device.

[0005] In some embodiments, the relationship curve between the capacity voltage differential dQ / dV and the voltage V of the electrochemical device during discharge comprises a peak A and a peak B above 3.8 V, wherein the peak position of peak A is in the range of 3.8 V to 4.1 V, the peak position of peak B is in the range of 4.1 V to 4.3 V, and the peak area of ​​peak A is S A , the peak area of ​​peak B is S B , satisfying: 0.5≤S B / S A≤1. Among them, peak A mainly depends on the second positive electrode active material, and peak B mainly depends on the first positive electrode active material. By adjusting the relative content of the first positive electrode active material and the second positive electrode active material, peak A and peak B satisfy 0.5≤S B / S A ≤1, which enables the electrochemical device to have both excellent cycle performance and safety performance. Further, in some embodiments, 0.5≤S B / S A ≤0.85.

[0006] In some embodiments, the relationship curve between the capacity-voltage differential dQ / dV and the voltage V of the electrochemical device during discharge further includes a peak C in the range of 3.5V to 3.7V. The presence of the peak C can further enable the electrochemical device to have a higher discharge capacity, thereby further improving the energy density of the electrochemical device.

[0007] In some embodiments, the relationship curve between the capacity-voltage differential dQ / dV and the voltage V of the electrochemical device during discharge includes at least one peak above 4.1 V. This indicates that the first positive electrode active material has a good reversible capacity in the high voltage region, thereby improving the cycle performance and safety performance of the electrochemical device.

[0008] In some embodiments, when the electrochemical device is in a fully charged state, the positive electrode plate is characterized by X-ray diffraction, and has a diffraction peak 1 in the range of 43.7° to 44.1°, and the peak intensity of diffraction peak 1 is P1, and has a diffraction peak 2 in the range of 44.2° to 44.6°, and the peak intensity of diffraction peak 2 is P2, satisfying: 1≤P2 / P1≤6.5. Among them, diffraction peak 1 corresponds to the first positive electrode active material, diffraction peak 2 corresponds to the second positive electrode active material, and P2 / P1 satisfies the above range, which enables the electrochemical device to have both excellent cycle performance and safety performance. Further, in some embodiments, 2.3≤P2 / P1≤6.5.

[0009] In some embodiments, the first positive electrode active material further contains an M1 element, M1 includes at least one of Na or K, based on the metal elements other than the Li element and the M1 element in the first positive electrode active material, the molar percentage of the Ni element in the first positive electrode active material is a1, the molar percentage of the Mn element is b1, and the molar percentage of the M1 element is c1, satisfying: 30%≤a1≤70%, 30%≤b1≤70%, 0.1%≤c1≤15%. The doping of the M1 element enables the first positive electrode active material to have good structural stability at high temperature and high voltage, thereby improving the cycle performance and safety performance of the electrochemical device.

[0010] In some embodiments, the second positive electrode active material further contains an M2 element, M2 includes at least one of Mn or Al, based on the metal elements other than the Li element in the second positive electrode active material, the molar percentage of the Ni element in the second positive electrode active material is a2, the molar percentage of the Co element is b2, and the molar percentage of the M2 element is c2, satisfying: 80%≤a2≤98%, 1%≤b2≤19%, 1%≤c2≤19%. The presence of the M2 element can improve the structural stability of the second positive electrode active material at high temperature and high voltage, thereby improving the cycle performance and safety performance of the electrochemical device.

[0011] In some embodiments, the first positive electrode active material is a secondary particle aggregated from primary particles, so as to improve the kinetic performance of the electrochemical device.

[0012] In some embodiments, the first positive active material has an average diameter of 6 μm to 14 μm.

[0013] In some embodiments, the second positive electrode active material is a primary particle, which can improve the structural stability of the second positive electrode active material at high temperature and high voltage, thereby improving the cycle performance and safety performance of the electrochemical device.

[0014] In some embodiments, the second positive active material has an average diameter of 3 μm to 10 μm.

[0015] In some embodiments, in a cross section in the thickness direction of the positive electrode active material layer, the area of ​​the first positive electrode active material in the region of 127 μm×34 μm is S1, and the area of ​​the second positive electrode active material is S2, satisfying: 0.5≤S2 / S1≤1.5. S2 / S1 satisfies the above range, enabling the electrochemical device to have both excellent cycle performance and safety performance. Further, in some embodiments, 0.7≤S2 / S1≤1.3.

[0016] In some embodiments, the first cathode active material has a layered crystal structure belonging to the R-3m space group. In some embodiments, the first cathode active material includes Li x1 M1 m Ni y1 Mn z1 R1 q1 O 2±n1 T1 n1, 0.6≤x1≤1.2, 0.001≤m≤0.15, 0.3≤y1≤0.7, 0.3≤z1≤0.7, 0≤q1≤0.2, 0≤n1≤0.2, wherein the element M1 includes at least one of Na or K, the element R1 includes at least one of Co, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and the element T1 includes at least one of F, Cl, Br, I or N.

[0017] In some embodiments, the second cathode active material has a layered crystal structure belonging to the R-3m space group. In some embodiments, the second cathode active material includes Li x2 Ni y2 Co z2 M2 p R2 q2 O 2±n2 T2 n2 , 0.6≤x2≤1.2, 0.8≤y2≤0.98, 0.01≤z2≤0.19, 0.01≤p≤0.19, 0≤q2≤0.1, 0≤n2≤0.2, wherein element M2 includes at least one of Mn or Al, element R2 includes at least one of Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Na, K, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and element T2 includes at least one of F, Cl, Br, I or N.

[0018] In a second aspect of the present application, an electronic device is also provided, comprising the above-mentioned electrochemical device. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and a person skilled in the art can also obtain other embodiments based on these drawings.

[0020] Figure 1 is a discharge curve of the electrochemical device of Example 1 of the present application;

[0021] Figure 2 A curve showing the relationship between the capacity-voltage differential dQ / dV and the voltage V of the electrochemical device of Example 1 of the present application during discharge;

[0022] Figure 3This is a scanning electron microscope (SEM) photograph of a cross section of the positive electrode sheet of Example 1 of the present application;

[0023] Figure 4 This is the X-ray diffraction (XRD) spectrum of the positive electrode sheet of the electrochemical device in Example 1 of the present application when it is fully discharged. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.

[0025] In a first aspect of the present application, an electrochemical device is provided, the electrochemical device comprising a positive electrode plate. The positive electrode plate comprises a positive electrode active material layer. The positive electrode active material layer comprises a first positive electrode active material and a second positive electrode active material. The first positive electrode active material comprises Ni element and Mn element, and the second positive electrode active material comprises Ni element and Co element. The relationship curve between the capacity voltage differential dQ / dV and the voltage V of the electrochemical device during discharge contains at least two peaks above 3.8V.

[0026] In the electrochemical device of the present application, the first positive electrode active material has a characteristic peak in the high voltage region of the relationship curve of the capacity-voltage differential dQ / dV and the voltage V during the discharge of the electrochemical device, relative to the second positive electrode active material, which can enable the electrochemical device to have a higher reversible discharge capacity in the high voltage region, thereby meeting the high energy density requirement of the electrochemical device; at the same time, since the amount of lithium desorption of the first positive electrode active material in the high voltage region is relatively high, the risk of excessive lithium desorption of the second positive electrode active material can be reduced, thereby improving the structural stability of the second positive electrode active material at high temperature and high voltage, and due to the presence of oxygen vacancies on the surface of the first positive electrode active material itself, its surface oxygen release can be inhibited, so that it still has a higher structural stability at high temperature and high voltage, thereby greatly improving the cycle performance and safety performance of the electrochemical device.

[0027] In some embodiments, the relationship curve between the capacity voltage differential dQ / dV and the voltage V of the electrochemical device during discharge comprises a peak A and a peak B above 3.8 V, wherein the peak position of peak A is in the range of 3.8 V to 4.1 V, the peak position of peak B is in the range of 4.1 V to 4.3 V, and the peak area of ​​peak A is S A , the peak area of ​​peak B is S B , satisfying: 0.5≤S B / S A ≤1. Among them, peak A mainly depends on the second positive electrode active material, peak B mainly depends on the first positive electrode active material, S B / S AIt can be used to indirectly characterize the mixing ratio of the first positive electrode active material and the second positive electrode active material. By adjusting the relative content of the first positive electrode active material and the second positive electrode active material, peak A and peak B satisfy 0.5≤S B / S A ≤1, which enables the electrochemical device to have both excellent cycle performance and safety performance. B / S A is 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, or any two of the above. Further, in some embodiments, 0.5≤S B / S A ≤0.85.

[0028] In some embodiments, the relationship curve between the capacity-voltage differential dQ / dV and the voltage V of the electrochemical device during discharge further includes a peak C in the range of 3.5V to 3.7V. The presence of the peak C can further enable the electrochemical device to have a higher discharge capacity, thereby further improving the energy density of the electrochemical device.

[0029] In some embodiments, the relationship curve between the capacity-voltage differential dQ / dV and the voltage V of the electrochemical device during discharge includes at least one peak above 4.1 V. This indicates that the first positive electrode active material has a good reversible capacity in the high voltage region, thereby improving the cycle performance and safety performance of the electrochemical device.

[0030] In some embodiments, when the electrochemical device is in a fully charged state, the positive electrode plate is characterized by X-ray diffraction, and has a diffraction peak 1 in the range of 43.7° to 44.1°, and the peak intensity of diffraction peak 1 is P1, and has a diffraction peak 2 in the range of 44.2° to 44.6°, and the peak intensity of diffraction peak 2 is P2, satisfying: 1≤P2 / P1≤6.5. Among them, diffraction peak 1 corresponds to the first positive electrode active material, and diffraction peak 2 corresponds to the second positive electrode active material. When P2 / P1 satisfies the above range, the electrochemical device can have excellent cycle performance and safety performance. Optionally, P2 / P1 is 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5 or a range composed of any two of the above. Further, in some embodiments, 2.3≤P2 / P1≤6.5. At this time, the cycle performance and safety performance of the electrochemical device are better.

[0031] In some embodiments, the first positive electrode active material further contains an M1 element, and M1 includes at least one of Na or K. The doping of the M1 element enables the first positive electrode active material to have good structural stability at high temperature and high voltage, thereby improving the cycle performance and safety performance of the electrochemical device.

[0032] In some embodiments, the M1 element is doped in the lithium layer, so as to better stabilize the crystal structure of the first positive electrode active material in a highly delithiated state, thereby improving the cycle performance and safety performance of the electrochemical device.

[0033] In some embodiments, based on the metal elements other than Li and M1 in the first positive electrode active material, the molar percentage of Ni in the first positive electrode active material is a1, the molar percentage of Mn is b1, and the molar percentage of M1 is c1, satisfying: 30%≤a1≤70%, 30%≤b1≤70%, 0.1%≤c1≤15%.

[0034] In some embodiments, the second positive electrode active material further contains an M2 element, M2 includes at least one of Mn or Al, based on the metal elements other than the Li element in the second positive electrode active material, the molar percentage of the Ni element in the second positive electrode active material is a2, the molar percentage of the Co element is b2, and the molar percentage of the M2 element is c2, satisfying: 80%≤a2≤98%, 1%≤b2≤19%, 1%≤c2≤19%. The presence of the M2 element can improve the structural stability of the second positive electrode active material at high temperature and high voltage, thereby improving the cycle performance and safety performance of the electrochemical device.

[0035] In some embodiments, the first positive electrode active material is a secondary particle aggregated from primary particles, so as to improve the kinetic performance of the electrochemical device.

[0036] In some embodiments, the first positive active material has an average diameter of 6 μm to 14 μm.

[0037] In some embodiments, the second positive electrode active material is a primary particle, which can improve the structural stability of the second positive electrode active material at high temperature and high voltage, thereby improving the cycle performance and safety performance of the electrochemical device.

[0038] In some embodiments, the second positive active material has an average diameter of 3 μm to 10 μm.

[0039] In some embodiments, in the cross section in the thickness direction of the positive electrode active material layer, the area of ​​the first positive electrode active material in the region of 127 μm×34 μm is S1, and the area of ​​the second positive electrode active material is S2, satisfying: 0.5≤S2 / S1≤1.5. In this way, the electrochemical device can have both excellent cycle performance and safety performance. Optionally, S2 / S1 is 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5 or a range of any two of the above. Further, in some embodiments, 0.7≤S2 / S1≤1.3. At this time, the cycle performance and safety performance of the electrochemical device are better.

[0040] In some embodiments, the first cathode active material has a layered crystal structure belonging to the R-3m space group. In some embodiments, the first cathode active material includes Li x1 M1 m Ni y1 Mn z1 R1 q1 O 2±n1 T1 n1 , 0.6≤x1≤1.2, 0.001≤m≤0.15, 0.3≤y1≤0.7, 0.3≤z1≤0.7, 0≤q1≤0.2, 0≤n1≤0.2, wherein the element M1 includes at least one of Na or K, the element R1 includes at least one of Co, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and the element T1 includes at least one of F, Cl, Br, I or N.

[0041] In some embodiments, the second cathode active material has a layered crystal structure belonging to the R-3m space group. In some embodiments, the second cathode active material includes Li x2 Ni y2 Co z2 M2 p R2 q2 O 2±n2 T2 n2 , 0.6≤x2≤1.2, 0.8≤y2≤0.98, 0.01≤z2≤0.19, 0.01≤p≤0.19, 0≤q2≤0.1, 0≤n2≤0.2, wherein element M2 includes at least one of Mn or Al, element R2 includes at least one of Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Na, K, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and element T2 includes at least one of F, Cl, Br, I or N.

[0042] In some embodiments, the positive electrode plate may further include a positive electrode current collector, in which case the positive electrode active material layer may be located on one or both sides of the positive electrode current collector. In some embodiments, the positive electrode current collector may include aluminum foil, and of course, other positive electrode current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive electrode current collector is 7 μm to 20 μm.

[0043] In some embodiments, the positive electrode active material layer may further include a conductive agent and a binder. In some embodiments, the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, or carbon nanofibers. In some embodiments, the binder may include at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, a styrene-acrylate copolymer, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene, or polyhexafluoropropylene. In some embodiments, the mass ratio of the positive active material, the conductive agent, and the binder in the positive electrode active material layer is (90-99):

[0044] (0.1-10):(0.1-10), but this is only an example, and any other suitable mass ratio may be used.

[0045] In some embodiments, the electrochemical device further comprises a negative electrode sheet and a separator, and the positive electrode sheet and the negative electrode sheet are separated by a separator disposed therebetween. In some embodiments, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer. In some embodiments, the negative electrode active material layer may be disposed on one side or both sides of the negative electrode current collector.

[0046] In some embodiments, the negative electrode active material layer may include a negative electrode active material, a binder, and an optional conductive agent. In some embodiments, the negative electrode active material may include at least one of a carbon material or a silicon-based material. In some embodiments, the carbon material includes at least one of graphite, hard carbon, soft carbon, or mesophase carbon microspheres. In some embodiments, the silicon-based material includes at least one of silicon, silicon-oxygen material, silicon-carbon material, or silicon-oxygen-carbon material.

[0047] In some embodiments, the binder in the negative electrode active material layer may include at least one of sodium carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyimide, polysiloxane, styrene-butadiene rubber, polyurethane resin or acrylate polymer. In some embodiments, the conductive agent in the negative electrode active material layer may include at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene or carbon nanofibers. In some embodiments, the mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode active material layer may be (78 to 98.5): (0.1 to 10): (0.1 to 10). It should be understood that the above is only an example, and any other suitable material and mass ratio may be used. In some embodiments, the negative electrode current collector may be at least one of copper foil, nickel foil or carbon-based current collector.

[0048] In some embodiments, the isolation membrane includes a porous substrate layer and a heat-resistant layer. In some embodiments, the porous substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polyimide, or aramid. In some embodiments, the thickness of the isolation membrane is in the range of 3 μm to 20 μm. In some embodiments, the pores of the porous substrate layer have a diameter in the range of 0.01 μm to 1 μm.

[0049] In some embodiments, the heat-resistant layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. The binder of the heat-resistant layer is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene, or polyhexafluoropropylene.

[0050] In some embodiments, the electrochemical device includes a lithium-ion battery, but the application is not limited thereto.

[0051] In some embodiments, the electrochemical device further comprises an electrolyte, the electrolyte comprising a lithium salt and a non-aqueous solvent. In some embodiments, the lithium salt comprises lithium hexafluorophosphate. In some embodiments, the concentration of the lithium salt is 1 mol / L to 2 mol / L. In some embodiments, the non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, or a combination thereof.

[0052] In certain embodiments, carbonate compounds can be linear carbonate compounds, cyclic carbonate compounds or combinations thereof. Examples of linear carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or combinations thereof. Examples of carboxylic acid ester compounds are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, caprolactone, methyl formate or combinations thereof. Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.

[0053] In the second aspect of the present application, an electronic device including the above-mentioned electrochemical device is also provided. The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a drone, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0054] Taking lithium-ion batteries as an example, some specific embodiments and comparative examples are listed below to better illustrate the present application.

[0055] Example 1

[0056] Preparation of negative electrode sheet: artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a mass ratio of 96:2:2 and dispersed in deionized water to prepare a negative electrode slurry with a solid content of 0.8. After stirring evenly, the negative electrode slurry is evenly coated on one side of the negative electrode current collector copper foil, and dried at 80°C to obtain a negative electrode sheet coated with a negative electrode active material layer on one side. Repeat the above steps on the other side of the copper foil to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides. After cold pressing, striping and welding of the pole ears, the negative electrode sheet is obtained.

[0057] Preparation of positive electrode sheet: positive electrode active material (including the first positive electrode active material and the second positive electrode active material, the mixing mass ratio is shown in Table 1), conductive carbon black, carbon nanotubes and polyvinylidene fluoride are mixed in a mass ratio of 93.7:2.8:1.2:2.3 and dispersed in N-methylpyrrolidone to prepare a positive electrode slurry with a solid content of 0.7. After fully stirring and mixing, the positive electrode slurry is evenly coated on one side of the positive electrode current collector aluminum foil, and dried at 85°C to obtain a positive electrode sheet coated with a positive electrode active material layer on one side, and the above steps are repeated on the other side of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides. After cold pressing, stripping, and welding of the pole ears, a positive electrode sheet is obtained.

[0058] The steps for preparing the first positive electrode active material are as follows:

[0059] 1) A mixed solution containing NiSO4 and MnSO4 is prepared according to the element molar ratio Ni:Mn=50:50, and the mixed solution is mixed with a precipitant (NaOH solution) and a complexing agent (ammonia water) for reaction, and the reaction time is controlled to be 60 hours, the ammonia concentration is 1 mol / L, and the pH value is 12.2 to obtain a nickel-manganese precursor TM(OH)2 (TM=Ni / Mn) with an average particle size Dv50 of 11 μm;

[0060] 2) Grind and mix the nickel-manganese precursor and sodium carbonate in a molar ratio of Na:(Ni+Mn) of 1.05:1. Calcine at 800°C in air for 20 hours, and then crush, screen and demagnetize to obtain product 1;

[0061] 3) mixing the product 1 with a mixture of lithium hydroxide and lithium nitrate (molar ratio of 1:1), wherein the mass ratio of the mixture of lithium hydroxide and lithium nitrate to the product 1 is 10:1, heating to 400°C at a rate of 10°C / min, maintaining for 6 hours, and quenching to room temperature in a mixture of Ar and air (the volume ratio of Ar to air is 1:2) at a cooling rate of 50°C / min to obtain the product 2;

[0062] 4) washing and soaking the second product in deionized water, and drying;

[0063] 5) Finally, after crushing and sieving, the first positive electrode active material is obtained, wherein the Na / (Ni+Mn)) molar ratio is 10.7%, and Dv50 is 9.4 μm.

[0064] The second positive electrode active material uses a single crystal high nickel ternary material LiNi with a Dv50 of 4.8um 0.9 Co 0.06 Mn 0.04 O2.

[0065] Preparation of isolation membrane: A porous polyethylene (PE) film with a thickness of 8 μm was selected as the isolation membrane.

[0066] Preparation of electrolyte: In an argon atmosphere glove box with a water content of less than 10 ppm, lithium hexafluorophosphate and a non-aqueous organic solvent (ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC): propyl propionate (PP): ethyl propionate (EP) = 1:1:1:1:1, weight ratio) are uniformly mixed to prepare an electrolyte, wherein the mass percentage of lithium hexafluorophosphate in the electrolyte is 12.5%.

[0067] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, shaping, etc.

[0068] The difference between Examples 2 to 13 and Example 1 is that the composition of the positive electrode active material is adjusted according to the mixing mass ratio of the first positive electrode active material and the second positive electrode active material shown in Table 1.

[0069] The difference between Comparative Example 1 and Example 1 is that the positive electrode active material only uses the first positive electrode active material.

[0070] The difference between Comparative Example 2 and Example 1 is that the positive electrode active material only uses the second positive electrode active material.

[0071] In addition, in this application, the following method is used to measure the corresponding parameters.

[0072] 1) Peak area:

[0073] In the voltage range of 2.8V to 4.35V, the lithium-ion battery is charged and discharged with a current of 0.1C to obtain the relationship curve between the discharge capacity voltage differential dQ / dV and the voltage V. Each peak in the curve is integrated to obtain the peak area of ​​each corresponding peak. For two partially overlapping peaks, the inflection point where the two peaks are connected is used for division.

[0074] 2) Particle morphology, average diameter and area ratio S2 / S1:

[0075] The positive electrode sheet was cut longitudinally using ion polishing, and then the morphology of the positive electrode active material particles in the cross section of the positive electrode sheet was observed using a scanning electron microscope (instrument model: ZEISS SEM, acceleration voltage: 0.1KV~30KV). In the cross-sectional photo, 50 first or second positive electrode active material particles were randomly selected, and the average value of their longest diameter was taken as the average diameter of the first or second positive electrode active material. In the cross-sectional photo, an area of ​​127μm×34μm was randomly selected, and the image software was used to count the area of ​​the first positive electrode active material as S1 and the area of ​​the second positive electrode active material as S2, thereby calculating the area ratio S2 / S1.

[0076] 3) Element content:

[0077] For the initial positive electrode active material, a mixed solvent was used to dissolve the first and second positive electrode active materials respectively (for example, 0.4 g of the positive electrode active material was dissolved in a mixed solvent of 10 ml of aqua regia (nitric acid and hydrochloric acid mixed in a ratio of 1:1) and 2 ml of HF), the volume was fixed to 100 mL, and then the content of each element in the solution was tested using an ICP analyzer.

[0078] For the first positive electrode active material and the second positive electrode active material in the positive electrode sheet, the positive electrode sheet was cut longitudinally using ion polishing, and then the cross-section of the positive electrode sheet was observed using a scanning electron microscope (instrument model: ZEISS SEM), and the first and second positive electrode active materials were tested respectively using an energy dispersive spectrometer (EDS) to determine the element content in the first positive electrode active material and the second positive electrode active material.

[0079] 4) X-ray diffraction:

[0080] The lithium-ion battery was fully discharged and disassembled to obtain the positive electrode piece, and the positive electrode piece was subjected to X-ray diffraction analysis using an X-ray diffractometer (instrument model: Bruker D8ADVANCE, target material: Cu Kα, scanning angle: 5-80°).

[0081] 5) Discharge capacity test:

[0082] The lithium-ion battery is first charged at a constant current of 0.5C at a constant temperature of 25°C. After charging to 4.35V, it is charged at a constant voltage to a current of 0.05C. Then, it is discharged at a constant current of 0.2C to 2.8V. The discharge gram capacity = the discharge capacity at 0.2C / the mass of the positive electrode active material.

[0083] 6) Cycle performance test:

[0084] First, in an environment of 45°C, the first charge and discharge were performed, first using a constant current charge of 0.5C to charge to 4.35V, then constant voltage charge to a current of 0.05C, and then constant current discharge at a current of 0.5C to discharge to 2.8V. Repeat the above charge and discharge cycles, and record the discharge capacity of the third cycle and the discharge capacity of the 500th cycle.

[0085] 45° C. cycle capacity retention rate=(discharge capacity at the 500th cycle / discharge capacity at the 3rd cycle)×100%.

[0086] 7) Acupuncture pass rate:

[0087] The lithium-ion battery is charged at a constant current of 0.5C to a voltage of 4.35V, and then charged at a constant voltage of 4.35V to a current of 0.05C, so that the lithium-ion battery reaches a fully charged state, and the appearance of the lithium-ion battery before the test is recorded. The battery is subjected to a nail penetration test in an environment of 25±3℃, with a steel nail diameter of 4mm and a penetration speed of 30mm / s. The nail penetration position is located at the geometric center of the lithium-ion battery plane. The test is stopped after 3.5min or when the battery surface temperature drops to 50℃. Ten lithium-ion batteries are grouped together, and the state of the lithium-ion battery during the test is observed. The lithium-ion battery passes the test if it does not burn or explode, and the needle penetration pass rate = the number of passes / 10.

[0088] 8)Hot box test pass rate:

[0089] Take 10 lithium-ion batteries for hot box test. Charge the lithium-ion batteries at a constant current of 0.5C to a voltage of 4.35V, then charge them at a constant voltage of 4.35V to a current of 0.05C, so that the lithium-ion batteries reach a fully charged state. Put the fully charged lithium-ion batteries into the test box, and heat the test box at a temperature rise rate of 5℃ / min. When the temperature in the box reaches (150±2)℃, keep the temperature constant and maintain it for 60 minutes. The lithium-ion batteries must not catch fire or explode to pass the test. Hot box test pass rate = pass number / 10.

[0090] Table 1 shows various parameters and evaluation results of Examples 1 to 13 and Comparative Examples 1 to 2.

[0091] Table 1

[0092]

[0093] By comparing Examples 1 to 13 and Comparative Example 2, it can be seen that compared with Comparative Example 2 which does not use the first positive electrode active material, the needle puncture pass rate and hot box pass rate of the lithium ion batteries of Examples 1 to 13 are significantly improved, which is beneficial to improving the safety performance of the lithium ion batteries.

[0094] By comparing Examples 1 to 13 and Comparative Example 1, it can be seen that the discharge gram capacity and cycle capacity retention rate of the lithium ion batteries of Examples 1 to 13 are significantly improved compared with Comparative Example 1 which does not use the second positive electrode active material.

[0095] In addition, by comparing Examples 1 to 13, it can be seen that when 0.5≤S B / S A When ≤0.85 or 2.3≤P2 / P1≤6.5, the cycle capacity retention rate, needle puncture pass rate and hot box pass rate of the lithium-ion battery are better. In addition, when 0.75≤S2 / S1≤1.3, the cycle capacity retention rate, needle puncture pass rate and hot box pass rate of the lithium-ion battery are better.

[0096] The above description is only a preferred embodiment of the present application and is not intended to limit the protection scope of the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application are included in the protection scope of the present application.

Claims

1. An electrochemical device, characterized in that A positive electrode sheet is included, wherein the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material, the first positive electrode active material contains Ni and Mn elements, and the second positive electrode active material contains Ni and Co elements; The relationship curve between the capacity-voltage differential dQ / dV and the voltage V during discharge of the electrochemical device includes at least two peaks above 3.8V.

2. The electrochemical device according to claim 1, characterized in that The relationship curve between the capacity voltage differential dQ / dV and the voltage V of the electrochemical device during discharge comprises a peak A and a peak B above 3.8 V, wherein the peak position of the peak A is in the range of 3.8 V to 4.1 V, the peak position of the peak B is in the range of 4.1 V to 4.3 V, and the peak area of ​​the peak A is S A , the peak area of ​​peak B is S B , satisfying: 0.5≤S B / S A ≤1; preferably, 0.5≤S B / S A ≤0.

85.

3. The electrochemical device according to claim 1, characterized in that At least one of the following conditions is met: (1) The relationship curve between the capacity-voltage differential dQ / dV and the voltage V of the electrochemical device during discharge also includes a peak C in the range of 3.5 V to 3.7 V; (2) A curve of the relationship between the capacity-voltage differential dQ / dV and the voltage V during discharge of the electrochemical device includes at least one peak above 4.1 V.

4. The electrochemical device according to claim 1, characterized in that When the electrochemical device is in a fully charged state, the positive electrode plate is characterized by X-ray diffraction, and has a diffraction peak 1 in the range of 43.7° to 44.1°, and the peak intensity of the diffraction peak 1 is P1. There is a diffraction peak 2 in the range of 44.2° to 44.6°, and the peak intensity of the diffraction peak 2 is P2, satisfying: 1≤P2 / P1≤6.

5.

5. The electrochemical device according to claim 4, characterized in that 2.3≤P2 / P1≤6.

5.

6. The electrochemical device according to claim 1, characterized in that The electrochemical device satisfies at least one of the following conditions: (1) The first positive electrode active material further contains an M1 element, M1 includes at least one of Na or K, and based on the metal elements other than Li and M1 in the first positive electrode active material, the molar percentage of Ni in the first positive electrode active material is a1, the molar percentage of Mn is b1, and the molar percentage of M1 is c1, satisfying: 30%≤a1≤70%, 30%≤b1≤70%, 0.1%≤c1≤15%; (2) The second positive electrode active material further contains an M2 element, M2 includes at least one of Mn and Al, based on the metal elements other than Li in the second positive electrode active material, the molar percentage of Ni in the second positive electrode active material is a2, the molar percentage of Co is b2, and the molar percentage of M2 is c2, satisfying: 80%≤a2≤98%, 1%≤b2≤19%, and 1%≤c2≤19%; (3) The first positive electrode active material includes Li x1 M1 m Ni y1 Mn z1 R1 q1 O 2±n1 T1 n1 , 0.6≤x1≤1.2, 0.001≤m≤0.15, 0.3≤y1≤0.7, 0.3≤z1≤0.7, 0≤q1≤0.2, 0≤n1≤0.2, wherein the element M1 includes at least one of Na or K, the element R1 includes at least one of Co, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and the element T1 includes at least one of F, Cl, Br, I or N; (4) The second positive electrode active material includes Li x2 Ni y2 Co z2 M2 p R2 q2 O 2±n2 T2 n2 , 0.6≤x2≤1.2, 0.8≤y2≤0.98, 0.01≤z2≤0.19, 0.01≤p≤0.19, 0≤q2≤0.1, 0≤n2≤0.2, wherein element M2 includes at least one of Mn or Al, element R2 includes at least one of Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Na, K, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and element T2 includes at least one of F, Cl, Br, I or N.

7. The electrochemical device according to claim 1, characterized in that The electrochemical device satisfies at least one of the following conditions: (1) The first positive electrode active material is a secondary particle aggregated from primary particles; (2) The average diameter of the first positive electrode active material is 6 μm to 14 μm; (3) The second positive electrode active material is a primary particle; (4) The average diameter of the second positive electrode active material is 3 μm to 10 μm.

8. The electrochemical device according to claim 1, characterized in that In the cross section of the positive electrode active material layer in the thickness direction, the area of ​​the first positive electrode active material in the region of 127 μm×34 μm is S1, and the area of ​​the second positive electrode active material is S2, satisfying: 0.5≤S2 / S1≤1.

5.

9. The electrochemical device according to claim 8, characterized in that 0.75≤S2 / S1≤1.

3.

10. An electronic device comprising the electrochemical device according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Cathode active material and method of manufacturing same, and nonaqueous electrolyte secondary battery

    CN109716564A

  • Positive active material for rechargeable lithium battery, method of preparing the same and rechargeable lithium battery including the same

    CN111668462A

  • Positive pole piece as well as electrochemical device and electronic device comprising positive pole piece

    CN115172694A

  • Positive electrode material, and electrochemical device and electronic device including positive electrode material

    CN116325219A

  • Positive electrode material, electrochemical device, and electronic device

    CN116802841A

Cited By

  • Secondary battery and electronic apparatus

    WO2026143350A1

  • Secondary battery and electronic apparatus

    WO2026165941A1